Problems of increasing the innovative professional training of future primary school teachers - Saydulloyeva Shoxsanam Mashrafjonovna; Omonillayeva Maxfuza Ilyosjon qizi (Genius Journals, 2023)
This article explores the challenges and issues associated with increasing the innovative professional training of future primary school teachers. It discusses various methods employed in such training, presents the results of these efforts, engages in a critical discussion of the findings, and concludes with suggestions for improvement
Keywords: Innovative professional training; primary school teachers; challenges; methods